The effects of transsphenoidal surgery on endocrine function and visual fields in patients with functionless pituitary tumours. - Harris, P; Afshar, F; Coates, P; Doniach, I; Wass, J; Besser, G; Grossman, A (1989)
Twenty-eight patients with functionless pituitary tumours have been treated by transsphenoidal surgery over the last 28 months. Mean age at presentation was 55 years. Tumor size was graded according to the extent of suprasellar extension on CT headscan from above the interclinoid line: four were small, 15 medium and nine large. Before surgery in 25 per cent of patients visual acuity and visual fields were normal. In the immediate postoperative period, 24 per cent of the patients with visual defects before surgery had normal vision, and in 38 per cent of the others it was improved. Six months after surgery, there had been further improvement; 43 per cent had normal vision and 48 per cent showed an overall improvement. In no patient did vision deteriorate following surgery. In the patients who presented with visual symptoms of one year or less, there was no correlation between the length of symptoms and the extent of visual recovery after surgery. Average age of the patients with full visual recovery was 47 +/- 4 years (mean +/- SEM); average age of the patients with only partial visual recovery was 63 +/- 3 years. Prolactin levels before surgery were elevated in 77 per cent of patients and fell significantly after operation, remaining elevated in 28 per cent of patients six months later. Fifty per cent of patients were treated with long-term hormone replacement therapy. Transsphenoidal surgery led to improved vision in the majority of patients, the results being comparable with those obtained with transfrontal surgery. Surgical complications were few, and long-term morbidity low. We suggest that the first-line treatment for patients with functionless pituitary tumours should be transsphenoidal surgery, even when large suprasellar extensions are present.